Metropolitan areas in Polan: Financial dimension - Maciej Turala (European Regional Science Association (ERSA), 2010)
A situation whereby the communes have the most efficient of income sources, including several local taxes, means that a metropolitan area - which is typically composed of several districts and several dozen communes - does not have a uniform and effective system of financing its activites. It may be claimed that the system of financing local governments in Poland ignores the metropolitan areas which appear in the Polish space, causing numerous negative implications for their functioning. The first part of the paper concentrates on how metropolitan areas are being shaped in Polish space, through an analysis of tax-based incomes of communes in seven regions (Dolnoslaskie, Kujawsko-Pomorskie, Lodzkie, Malopolskie, Pomorskie, Slaskie and Wielkopolskie). The second part of the paper refers to the growing importance of metropolitan areas for the development of European space and their common perception as engines of economic growth and sustainable development in Europe. Based on the above a research hypothesis has been formulated: a mechanism for equalising incomes of local governments which has been set up within the equalising part of general grants favours the communes which are located in the peripheries with regards to the metropolitan cities and their metropolitan areas. The author attempts to verify this hypothesis through an analysis of data on the amounts of the equalising part of the general grant which communes receive or are expected to transfer to the state budget between 2007 and 2009.
Keywords: 330